Sustainability assessment of universities as small-scale urban systems: A comparative analysis using Fisher Information and Data Envelopment Analysis. (1st March 2019) - Ai, Ning; Kjerland, Marc; Klein-Banai, Cynthia; Theis, Thomas L.
Abstract: This study aims to identify and implement appropriate techniques for a sustainability assessment, which corresponds to the optimal balance between efficiency and resilience. Strategies are discussed to fill two important gaps: (1) applicable methods for identifying and analyzing multiple variables for a "metabolic" assessment of urban systems over time; and (2) empirical data that can characterize multiple sub-components (e.g., environmental, financial, and institutional) of an urban system, especially at a refined geographic scale where data challenges are significant. With a specific focus on data integration, two methods, Fisher Information (FI) and Data Envelopment Analysis (DEA), were chosen for this study. Data analyses were implemented in an urban university, which provides valuable opportunities for enhancing our understanding of this type of urban system and enabling data-driven studies of neighborhood sustainability. Based on the strengths and weakness of FI and DEA identified in the empirical study, it is concluded that these two methods can be valuable yet complementary for an integrated system analysis. Highlights: Applied an urban metabolism approach for an integrated sustainability assessment. Identified and implemented FI and DEA for quantitative analysis. Demonstrated potentials of examining urban universities as small-scale systems. Suggested that FI and DEA can be valuable yet complementary methods.